The studies of the excitation functions of reactions with emission of γ - quanta induced by protons with energy 200...1800 keV on nuclei of ¹⁰B and ¹¹B - Levenets, V.V.; Omelnik, O.P.; Shchur, A.O. (Вопросы атомной науки и техники, 2022)
A systematic study of the relative thick-target yields of prompt γ-rays with the energies of the most suitable for elemental and isotopic analysis for stable boron isotopes following proton bombardment has been carried out at Ep = 200…1800 кeV. The relevant excitation function of γ-emission 429 keV from reaction ¹⁰B(p,αγ)⁷Be, 718 keV from reaction ¹⁰B(p,p′γ)¹⁰B, 4.439 and 16.106 MeV from reaction ¹¹B(p,γ)¹²C are depicted and a tables of yields of prompt γ-rays as function of proton bombardment energy are given. The experimental procedure is described. Particular aspects of the measuring techniques are discussed. Проведено систематичне дослідження відносних виходів з товстої мішені миттєвого γ-випромінювання з енергіями найбільш придатними для елементного та ізотопного аналізів стабільних ізотопів бору при бомбардуванні протонами з енергіями Ep = 200…1800 кеВ. Відповідні функції збудження γ-випромінювання 429 кеВ з реакції ¹⁰B(p,αγ)⁷Be, 718 кеВ з реакції ¹⁰B(p,p′γ)¹⁰B, 4,439 та 16,106 МеВ з реакції ¹¹B(p,γ)¹²C зображено на рисунках, та наведено таблиці виходів миттєвого γ-випромінювання залежно від енергії протонів. Описано методику експерименту. Обговорюються окремі аспекти вимірювальної техніки. Проведено систематическое исследование относительных выходов мгновенных γ-излучения из толстых мишеней с энергиями, наиболее подходящими для элементного и изотопного анализов стабильных изотопов бора при бомбардировке протонами при Ep = 200…1800 кэВ. Соответствующие функции возбуждения γ-излучения 429 кэВ из реакции ¹⁰B(p,αγ)⁷Be, 718 кэВ из реакции ¹⁰B(p,p′γ)¹⁰B, 4,439 и 16,106 МэВ из реакции ¹¹B(p,γ)¹²C изображены на рисунках, и даны таблицы выходов мгновенных γ-излучения в зависимости от энергии протонов. Описана методика эксперимента. Обсуждаются отдельные аспекты методов измерения.